2014
DOI: 10.1002/2013wr015236
|View full text |Cite
|
Sign up to set email alerts
|

A dynamical system perspective on plant hydraulic failure

Abstract: Photosynthesis is governed by leaf water status that depends on the difference between the rates of transpiration and water supply from the soil and through the plant xylem. When transpiration increases compared to water supply, the leaf water potential reaches a more negative equilibrium, leading to water stress. Both high atmospheric vapor pressure deficit and low soil moisture increase the water demand while decreasing the supply due to lowered soil-to-root conductance and xylem cavitation. Therefore, dry c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 58 publications
0
39
0
Order By: Relevance
“…VWC is usually exponentially related to Ψ L (Pearcy et al ., ; Zweifel et al ., ). Such negative exponential relationships and their close relative, the Weibull function, have previously been successfully linearized in the study of leaf water potential dependencies (Manzoni et al ., ; Martinez‐Vilalta et al ., ; Gentine et al ., ) supporting the following approximation VWC = α normalΨ normalL + β …”
Section: Methodsmentioning
confidence: 99%
“…VWC is usually exponentially related to Ψ L (Pearcy et al ., ; Zweifel et al ., ). Such negative exponential relationships and their close relative, the Weibull function, have previously been successfully linearized in the study of leaf water potential dependencies (Manzoni et al ., ; Martinez‐Vilalta et al ., ; Gentine et al ., ) supporting the following approximation VWC = α normalΨ normalL + β …”
Section: Methodsmentioning
confidence: 99%
“…In the case of isohydric species, like Acer saccharum , the most immediate response to low soil water availability is the closure of stomata to better maintain a constant level of leaf turgor (Manzoni et al. ). If drought remains for long periods of time, the major effect is decreased photosynthetic assimilation and reduced radial growth (Bahari et al.…”
Section: Introductionmentioning
confidence: 99%
“…Stomata integrate the environmental and hydraulic signals external and internal to the plant including the xylem flow pathway from the roots to the guard cells (Meinzer et al, ; Woodruff, Meinzer, & McCulloh, ). Using a simple plant hydraulic model, Manzoni et al () showed that the coordination among plant hydraulic traits results in an increased resilience to environmental stresses. For example, deep roots in anisohydric species make them less vulnerable to hydraulic failure, whereas the impact of deeper roots on carbon deficiency is only marginal (Figure b,d,f).…”
Section: Resultsmentioning
confidence: 99%